Trigonometry 7th Edition

Published by Cengage Learning
ISBN 10: 1111826854
ISBN 13: 978-1-11182-685-7

Chapter 2 - Section 2.1 - Definition II: Right Triangle Trigonometry - 2.1 Problem Set: 39

Answer

1

Work Step by Step

Given expression = $ \sin^{2} 60^{\circ} + \cos^{2} 60^{\circ}$ = $ ( \sin 60^{\circ})^{2} + ( \cos 60^{\circ})^{2}$ = $ (\frac{\sqrt 3}{2})^{2} + (\frac{1}{2})^{2}$ ( substituting for exact values of $ \sin 60^{\circ}$ and $ \cos 60^{\circ})$ =$ \frac{3}{4} + \frac{1}{4}$ = $\frac{(3+1)}{4}$ = $ \frac{4}{4}$ = 1
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.